2012
DOI: 10.1002/cbic.201200336
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Mutational Study of an Archaeal DNA Ligase towards Improvement of Ligation Activity

Abstract: DNA ligases catalyze the joining of strand breaks in duplex DNA. The DNA ligase of Pyrococcus furiosus (PfuLig), which architecturally resembles the human DNA ligase I (hLigI), comprises an N-terminal DNA-binding domain, a middle adenylylation domain, and a C-terminal oligonucleotide-binding (OB)-fold domain. Here we addressed the C-terminal helix in the OB-fold domain of PfuLig by mutational analysis. The crystal structure of PfuLig revealed that this helix stabilizes a closed conformation of the enzyme by fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…Interestingly, the results of DNA ligation assays suggest that the residues 610–620 are important for the enzymatic activity of LigIV (Figure S1C). A recent report also suggests that the C-terminal helix of an archaeal DNA ligase is important for its activity (Tanabe et al., 2012). …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the results of DNA ligation assays suggest that the residues 610–620 are important for the enzymatic activity of LigIV (Figure S1C). A recent report also suggests that the C-terminal helix of an archaeal DNA ligase is important for its activity (Tanabe et al., 2012). …”
Section: Resultsmentioning
confidence: 99%
“…5A)24. When the ratio of the substrate DNA to PfuPCNA/PfuLig was relatively low, no facilitation of the nick-ligation was observed even with the wild type PfuPCNA, whereas the facilitation effect by PfuPCNA was detected in the presence of a large excess of the substrate.…”
Section: Resultsmentioning
confidence: 97%
“…The reactions were initiated by the addition of the enzymes, and were halted by the addition of a stop reagent (20 mM EDTA and 90% formamide). The samples were heated at 95 °C for 5 min and then electrophoresed through an 11% polyacrylamide gel containing 8 M urea in TBE (89 mM Tris/Tris-borate; 2 mM EDTA)2429. The quantities of the products in the ligation reaction were estimated from the fluorescent band intensities on the gel, obtained with a FluoroImager 595 (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…We previously searched for an effective substitution in the C‐terminal extension helix region to improve the nick‐joining activity, and found that point mutations of Asp540, and especially the replacement with a basic residue (D540R), significantly enhanced the enzymatic activity. However, unexpectedly, D540R showed a much higher Δ H value than that of the wild type for substrate DNA binding, thus implying that the DNA‐binding process involves unfavorable bond disruption in D540R [13].…”
Section: Introductionmentioning
confidence: 93%